Analyzing the Theme as Intrinsic Elements in Short Story Entitled “Runaway” by Alice Munro - Negara, I Putu Suwita Adi; Rajeg, I Made; Maharani, Sang Ayu Isnu (IAI Nasional Laa Roiba Bogor, 2024)
Short story in literature is a brief work of fiction that usually focused on a single plot, theme, or character. Short story has intrinsic elements like novel, and they are: plot, theme, setting, point of view, character and characterization, and symbol. This research paper aimed to analyze the intrinsic elements specifically the theme in a short story “Runaway” by Alice Munro. In this study, the data source is collected from the short story by Alice Munro entitled “Runaway”. The researcher uses qualitative method and theory of literature by Wellek and Warren to analyze and describe the result of this research. In Alice Munro's